Comparative analysis of the antimicrobial activity of peracetic acid and sodium hypoclorite in the fight against Staphylococcus aureus (Research, Society and Development, 2022)
Analyze compared to antimicrobial activity of peracetic acid and sodium hypochlorite against S. aureus, showing the best reagent in the inhibition of the same, in addition to quantify the concentration minimum required to inhibition growth. methodology: for the experimental group I (peracetic acid), were used 10 microtubes getting 900μl reagent and dilutions serial of 10-1 to 10-9, for the experimental group II (sodium hypochlorite) another 10 microtubes received 900μl reagent and dilutions serial of 10-1 to 10-9. It was added more 100μl the inoculum bacterial to microtubes of both groups, the mixture was incubated greenhouse bacteriological for 5 minutes at 37ºc and later sown in culture medium. The peracetic acid showed efficiency inhibition of growth of S. aureus to the dilution of 10-2, this being dilution the 0,001% of peracetic acid. In dilution of 10-3 there was a growth part of 44% compared to the control group, in dilutions later there was 100% bacterial growth. sodium hypochlorite showed effectiveness to the dilution of 10-4 being this dilution corresponding to the sodium hypochlorite the 0,0001%. In dilution of 10-5 sodium hypochlorite had an effect partial 86% of bacterial growth in relation to the control group, in dilutions later there was 100% bacterial growth. The Sodium hypochlorite showed be ten times more effective than the peracetic acid in relation to inhibition of growth of Staphylococcus aureus.